Global research trends in digital technology and financial inclusion: A bibliometric approach - Jumbri, Isma Addi; Hanafi, Mamduh M.; Pahlevi, Reza Widhar; Resmi, Siti (IPMEDIA SDN BHD, 2025)
This study examines how research on digital technology and financial inclusion has evolved between 2005 and 2022 through a bibliometric analysis of 291 Scopus-indexed publications. Using Microsoft Excel and VOSviewer, it evaluates publication trends, influential authors and institutions, and the intellectual structure of the field. The findings show that contributions were modest in the early years but expanded rapidly after 2017, supported by fintech adoption, global development agendas, and the acceleration of digital financial services during the COVID-19 pandemic. Three main streams of research are identified: financial technology and innovation, including mobile banking and blockchain; technology adoption and institutional factors; and social inclusion and financial literacy, emphasising trust, equity, and cultural acceptance. These streams demonstrate that digital financial inclusion is shaped not only by technological and economic factors but also by social and cultural dimensions. Despite substantial progress, challenges such as digital divides, limited skills, and regulatory gaps constrain equitable access, while emerging frontiers link digital finance with sustainability and green innovation. By mapping these developments, the study contributes a roadmap for future research. It offers practical insights for policymakers, financial institutions, and development agencies working to harness digital technologies for inclusive and sustainable growth.